Green Extraction of Lignin Compounds from Sugarcane Bagasse Waste for Eco-Friendly Sunscreen Cream Development - Melisa Nur Halimah; Teguh Pambudi; Hilman Imadul Umam; Fajar Amelia Rachmawati Putri (Berkala Sainstek)
This study aimed to develop a lignin extraction method from sugarcane bagasse (SCB), considering the high potential of lignin as an active ingredient in natural sunscreen formulations. Indonesia, as one of the largest sugarcane producers, generates abundant SCB waste that is often underutilized, despite its significant lignin content. By valorizing this biomass, the approach is expected to support zero-waste principles and sustainability in the cosmetic industry. Lignin extraction was conducted using a green process based on Deep Eutectic Solvent (DES) and compared to the conventional NaOH-based method. Characterization was performed using FTIR spectroscopy to identify functional groups and UV-Vis spectrophotometry to evaluate UV absorption ability. The results showed that lignin extracted using DES exhibited sharper FTIR peaks in the 1000-1200 cm⁻¹ region, indicating higher phenolic and C-O group content compared to NaOH-extracted lignin. In the UV-Vis analysis, the maximum absorbance of DES-extracted lignin was at 4% concentration in the UV-A and UV-B regions, suggesting effective protection against UV radiation. In addition to yielding high-quality lignin, the DES method minimized the use of hazardous chemicals. These findings demonstrate that DES-extracted lignin holds great promise as a natural active agent in environmentally friendly sunscreen formulations, supporting the growing trend toward sustainable cosmetics and offering a safer alternative to conventional synthetic ingredients.